Efficacy and safety of methylprednisolone pulse followed by oral prednisone vs. oral prednisone alone in sarcoidosis tubulointerstitial nephritis: a randomized, open-label, controlled clinical trial. Issue 4 (6th September 2022) - Mahevas, Matthieu; Audard, Vincent; Rousseau, Alexandra; Cez, Alexandre; Guerrot, Dominique; Verhelst, David; Delahousse, Michel; Hanrotel, Catherine; Pillebout, Evangeline; Daugas, Eric; Krastinova, Evguenia; Valeyre, Dominique; et al.
ABSTRACT: Background: We determine the benefit of pulsed methylprednisolone for improving kidney function in patients with sarcoidosis tubulointerstitial nephritis. Methods: We conducted a multicenter, prospective, randomized, open-label, controlled trial in patients with biopsy-proven acute tubulointerstitial nephritis caused by sarcoidosis at 21 sites in France. Patients were randomly assigned to receive a methylprednisolone pulse 15 mg/kg/day for 3 days, then oral prednisone (MP group) or oral prednisone 1 mg/kg/day alone (PRD group). The primary end point was a positive response at 3 months, defined as a doubling of estimated glomerular filtration rate (eGFR) compared with the eGFR before randomization. Results: We randomized 40 participants. Baseline eGFR before PRD was 22 mL/min/1.73m 2 interquartile range [IQR], 16–44 and before MP was 25 mL/min/1.73m 2 (IQR, 22–36) ( P = .3). The two groups did not differ in underlying pathological lesions, including mean percentage of interstitial fibrosis and intensity of interstitial infiltrate. In the intent-to-treat population, the median eGFR at 3 months did not significantly differ between the PRD and MP groups: 45 (IQR, 34–74) and 46 (IQR, 39–65) mL/min/1.73m 2 . The primary end point at 3 months was achieved in 16 of 20 (80%) PRD patients and 10 of 20 (50%) MP patients ( P = .0467). The eGFR was similar between the two groups after 1, 3, 6, and 12 months of treatment. For both groups, eGFR at 1 month was strongly correlated with eGFR at 12 months ( P < .0001). The two groups did not differ in severe adverse events. Conclusion: Compared with a standard oral steroid regimen, intravenous MP may have no supplemental benefit for renal function in patients with tubulointerstitial nephritis caused by sarcoidosis. Trial Registration: ClinicalTrials.gov : NCT01652417; EudraCT: 2012–000149-11